2021
DOI: 10.1136/tobaccocontrol-2021-056633
|View full text |Cite
|
Sign up to set email alerts
|

Policy incoherence and tobacco control in Indonesia: an analysis of the national tobacco-related policy mix

Abstract: IntroductionIndonesia has a high smoking prevalence that has not diminished significantly since 1990. Considering this, we aim to summarise the existing national tobacco-related policy mix and explore markers of policy incoherence in tobacco control between 2014 and 2020.MethodsWe conducted (1) a review and synthesis of Indonesian tobacco-related legislation and regulations; (2) a systematic search and synthesis of related literature and news reporting; and (3) interviews with tobacco control activists and aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The findings also revealed how political factors hinder tobacco control in LMICs in the region, including lack of enforcement of TAPS restrictions, insufficient fines to deter violations, and lack of government leadership to institutionalize tobacco control. While these results align with what has been revealed in Indonesia 22,23 , the current study suggests that these challenges occur more broadly throughout LMICs in the ASEAN region.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings also revealed how political factors hinder tobacco control in LMICs in the region, including lack of enforcement of TAPS restrictions, insufficient fines to deter violations, and lack of government leadership to institutionalize tobacco control. While these results align with what has been revealed in Indonesia 22,23 , the current study suggests that these challenges occur more broadly throughout LMICs in the ASEAN region.…”
Section: Discussionsupporting
confidence: 91%
“…According to one study, policy adoption in Indonesia had been constrained by the industry’s lobbying practices, a complex bureaucratic process, political corruption, and the relatively low bargaining power and resources of the Ministry of Health and tobacco control advocates 22 . Further work utilizing document analysis and interviews with tobacco control experts demonstrated that Indonesia’s tobacco-related policy mix was fragmented across various ministries, which lacked the political will, institutional processes, and an overarching national framework to implement an effective policy response 23 . While these findings illustrate some of the factors influencing tobacco control in Indonesia, the only ASEAN country yet to ratify the FCTC, to the authors’ knowledge, no studies have explored experts’ insights on tobacco industry interference in ASEAN LMICs that have adopted the FCTC convention and are pursuing policies in line with its articles.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for choosing these diverse commodities as the focus of the study is to investigate the political economy in light of their distinct attributes and characteristics. Furthermore, our focus is exclusively on the sub-national level, as there is an abundance of evidence regarding the political economy of health taxation in Indonesia at the national level (20,21,23,(36)(37)(38)(39). The next section will describe the methodology and analytical approach used in this study, followed by results, and finally discussion and future recommendation.…”
Section: The Current Status Of Health Tax Implementation In Indonesiamentioning
confidence: 99%
“…Local governments have emerged as important sites for tobacco regulation around the world (Ackerman et al, 2016; Enrich and Davidson, 1998). In Indonesia, since national laws pertaining to health require local legislatures to issue implementing regulations, local governments are, essentially, required to play a role in tobacco control (Kramer et al, 2021). This particular responsibility applies to the implementation of Government Regulation (Peraturan Pemerintah, PP) No.…”
Section: Creating Subnational Laws In a Decentralised Indonesiamentioning
confidence: 99%